How To Choose Suitable English Coursebooks To Be Used In The English Teaching-Learning Process: Doing A Micro Evaluation - Muhammad, Kharis Sukarno (Journal of English and Education (JEE), 2008)
English course books are one of the main elements determining the success of the English teaching-learning process to meet the pre-determined objectives. Currently, the teachers of, English in Indonesia face a  complicated tasks in choosing suitable English teaching materials in die form of English course books. The purpose of the article is to discuss an appropriate way to choose English course books suitable with the students' socio-economic cultural backgrounds to facilitate students' learning. The intended way is that the teachers of English do an empirical evaluation of the course books they are using, a retrospective evaluation. The evaluation can be done through either macro or micro evaluation. The tangible and practical evaluation to do is a micro evaluation in which the teachers of English retrospectively and thoroughly evaluate certain parts of the English course books representing the whole content The criteria to valuate include goals, students' backgrounds (topics and vocabulary related to students' lives), cultural acceptability, language skills to develop quality of practical materials in the classroom (activating students' participation), roles, sequencing of the materials (procedure), formats, instructions, and visualization. If the teachers of English find out such English course books through their evaluation, they can use the course books in the following terms. It a wise way to choose English course books to be used to optimally reach the pre-determined objectives. If the teachers of English do not find such suitable English course books through their evaluation, they can add materials to or reduce the content of the course booksand finally they will have teachers' edition English teaching materials.